Frontiers of Asset Pricing - Kolari, James W.; Pynnonen, Seppo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is comprised of articles published in a Special Issue of the Journal of Risk and Financial Management entitled "Frontiers in Asset Pricing" with Guest Editors Professor James W. Kolari and Professor Seppo Pynnonen. The book contains papers in various areas related to asset pricing: (1) models; (2) multifactors; (3) theory; (4) empirical tests; (5) applications; (6) other asset classes; and (7) international tests.